Transesterification Between Diphenyl Carbonate and 1,6-Hexandiol Catalyzed by Metal-Organic Frameworks Based on Zn2+ and Different Aromatic Carboxylic Acids - Wang, Liping; Wang, Gongying; Wang, Fan; Liu, Pinhua (Asian Journal of Chemistry, 2013)
Metal-organic frameworks based on metal ion Zn2+ and different aromatic carboxylic acid ligands were prepared by the solvothermal method and characterized by X-ray diffraction and Fourier transform infrared spectroscopy. They were then used as the catalysts for the preparation of polycarbonate diol via the transesterification between diphenyl carbonate and 1,6-hexandiol. Their catalytic activities in the transesterification process were evaluated by the yield of phenol and their catalytic activities in the polycondensation process were determined by the number-average molecular weight (Mn) and the hydroxyl value. The experimental results show that metal-organic frameworks made from Zn2+ with benzene-1,4-dicarboxylic acid and benzene-1, 3, 5-tricarboxylic acid exhibit higher catalytic activities than metal-organic frameworks made from Zn2+ with benzene-1,3-dicarboxylic acid and benzene-1,2-dicarboxylic acid for the preparation of polycarbonate diol.